THE USE SHOW AND TELL (S&T) METHOD IN TEACHING SPEAKING ENGLISH SKILLS FOR STUDENTS OF SENIOR HIGH SCHOOL 6 SOPPENG (Karya Ilmiah Mahasiswa (KIMA), 2022)
Show and Tell (S&T) Method is an action research study which comprised two ways in teaching speaking. This research use Picture as an object to describe. This research involved me as the researcher, the principle of SMAN 6 Soppeng, the English teacher and 35 students of XII IPA 2 class of SMAN 6 Soppeng in the academic year 2021-2022. the aims of this research are to find out the students speaking improvement and the problem when using Show and Tell (S&T) Method. The data of this research are quantitative and qualitative (mix method). The quantitative data were implementation of the Observing the students action when do this method. The quantitative data were taken by Observation Checklist to know students speaking ability and students improvement by using Show and Tell (S&T) Method through the pre test and post test which is in the form an score , Microsoft Excel and Spss. The qualitative data was implementing in the last meeting, the data were taken by questionnaire to know students problem in speaking by using Show and Tell (S&T) Method. The researcher find that using Show and Tell (S&T) Method is effective to improve students speaking skills by using some picture and push the students to speak based on the picture. Show and Tell (S&T) Method makes students stronger in remembering sentences to be presented in front of their classmates. The steps when teaching speaking with this method are make students enjoy and interesting in learning more about English.